UJI AKTIVITAS SABUN MANDI HERBAL ECOENZYME SEBAGAI ANTISEPTIK ALAMI TERHADAP Staphylococcus aureus DAN Propionibacterium acne - Tahir, Muhammad (Jurnal Kesehatan Yamasi Makassar, 2025)
Evaluation of the Antiseptic Activity of Herbal Bath Soap Containing Eco Enzyme Against Staphylococcus aureus and Propionibacterium acnes. Herbal bath soap is a skin cleanser formulated with a soap base and permitted additives to enhance its functionality and consumer appeal. The use of natural ingredients, particularly fruit and vegetable waste, offers a sustainable source of active compounds. Through fermentation, these materials can be converted into eco enzyme, which contains various bioactive substances with potential antibacterial properties. This study aimed to assess the antibacterial activity of herbal bath soap formulated with eco enzyme against Staphylococcus aureus and Propionibacterium acnes. The inhibition zone assay demonstrated that soap containing 25% and 50% eco enzyme exhibited average inhibition zones of 1.596 mm and 1.69 mm against P. acnes, respectively, while the negative control produced a zone of 0.88 mm. For S. aureus, the inhibition zones at the same concentrations were 3.44 mm and 1.997 mm. These findings suggest that eco enzyme-based herbal bath soap exhibits antibacterial effects against both tested bacterial strains. However, the observed inhibition remains within the weak category (<5 mm), indicating a limited but measurable antibacterial potential.